Performance and Characterization for Blend Membrane of PES with Manganese(III) Acetylacetonate as Metalorganic Nanoparticles - H. Abdallah; M. S. Shalaby; A. M. H. Shaban (International Journal of Chemical Engineering)
This study describes the preparation, characterization, and evaluation of performance of blend Polyethersulfone (PES) with manganese(III) acetylacetonate Mn(acac)3 to produce reverse osmosis blend membrane. The manganese(III) acetylacetonate nanoparticles were prepared by a simple and environmentally benign route based on hydrolysis of KMnO4 followed by reaction with acetylacetone in rapid stirring rate. The prepared nanoparticle powder was dissolved in polymer solution mixture to produce RO PES/Mn(acac)3 blend membrane, without any treatment of Polyethersulfone membrane surface. The membrane morphology, mechanical properties, and performance were presented. The scanning electron microscopy (SEM) images have displayed a typical asymmetric membrane structure with a dense top layer due to the migration of Mn(acac)3 nanoparticles to membrane surface during the phase inversion process. Contact angle measurements have indicated that the hydrophilicity of the membrane was improved by adding Mn(acac)3. AFM images have proved excellent pores size distribution of blend membrane and lower surface roughness compared with bare PES. The desalination test was applied to blend membrane, where the blend membrane provided good performance; particularly, permeate flux was 24.2 Kg/m2·h and salt rejection was 99.5%.